2022
DOI: 10.1177/17474930221140792
|View full text |Cite
|
Sign up to set email alerts
|

Human blood metabolites and lacunar stroke: A Mendelian randomization study

Abstract: Background: Lacunar stroke accounts for a quarter of all strokes but little is known about the underlying pathological mechanisms. Analysis of serum metabolites may allow better understanding of the underlying biological processes. Mendelian randomization (MR) can provide information on the causality of associations. Aims: To identify causal relationships between serum metabolites and lacunar stroke. Methods: We applied a two-sample Mendelian randomization (MR) analysis to evaluate relationships between 486 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…For MR analyses, the genetic variants utilized must be representative of the characteristics of IgD-D24-AC and 1 https://www.finngen.fi/en AA2S. Based on previous similar studies (49,50), we selected single nucleotide polymorphisms (SNPs) with p values less than (1 × 10 −5 ) as instrumental variables (IVs) to make them more informative. Furthermore, SNPs that exhibited a linkage disequilibrium (LD) coefficient (r 2 ) of less than 0.001 and those positioned more than 10,000 kilobases apart were chosen to ensure independence.…”
Section: Instrumental Variable Selection and Data Harmonizationmentioning
confidence: 99%
“…For MR analyses, the genetic variants utilized must be representative of the characteristics of IgD-D24-AC and 1 https://www.finngen.fi/en AA2S. Based on previous similar studies (49,50), we selected single nucleotide polymorphisms (SNPs) with p values less than (1 × 10 −5 ) as instrumental variables (IVs) to make them more informative. Furthermore, SNPs that exhibited a linkage disequilibrium (LD) coefficient (r 2 ) of less than 0.001 and those positioned more than 10,000 kilobases apart were chosen to ensure independence.…”
Section: Instrumental Variable Selection and Data Harmonizationmentioning
confidence: 99%
“…Yi Feng et al have used MR to investigate the causal association of blood metabolites with lung cancer, breast cancer, ovarian cancer, and glioma, and identified 132 metabolites that may have a causal role in cancer progression 17 . Other MR studies have identified risk and protective serum metabolites associated with lacunar stroke 18 . MR provides a more convenient method for investigating the factors that influence disease.…”
Section: Introductionmentioning
confidence: 99%
“…For the relationship between cancers and blood metabolomic, Guo et al. applied two-sample MR to identify blood metabolites associated with lacunar stroke, finding 15 known and 14 unknown metabolites with potential implications in disease pathogenesis ( 20 ). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Chen et al identified a possible causal link between inflammatory bowel disease and oral cavity cancer (15). For the relationship between cancers and blood metabolomic, Guo et al applied two-sample MR to identify blood metabolites associated with lacunar stroke, finding 15 known and 14 unknown metabolites with potential implications in disease pathogenesis (20). Liu et al utilized bidirectional Mendelian randomization on Chinese individuals, revealing 58 causal relationships between the gut microbiome and blood metabolites, with a notable link between fecal Oscillibacter and Alistipes and decreased triglyceride concentration (21).…”
Section: Introductionmentioning
confidence: 99%